The 'Gulliver' fish fauna of an early Miocene freshwater system of New Zealand; new insights from otoliths from the Bannockburn Formation. Issue 1 (2nd January 2023) - Schwarzhans, Werner; Paul Scofield, R.; Tennyson, Alan J. D.; Worthy, Jennifer P.; Worthy, Trevor H.
ABSTRACT: The early Miocene palaeolake Manuherikia in Central Otago, South Island, New Zealand is a prime source for reconstructing the terrestrial and freshwater biota of past Zealandia. Otoliths of fishes that once lived in this lake system were first described in 2012. Here we report the results of extensive additional sampling resulting in a total of 16, 500 fish otoliths from a wide set of stratigraphic levels and environmental settings within the Bannockburn Formation near St Bathans. Six new species are described: Galaxias crassus, Galaxias naviculus, Galaxias nitidus, Galaxias polei, Galaxias tholus, Mataichthys asymmetricus . The entire freshwater otolith-based fish fauna of the Bannockburn Formation now encompasses 17 species, 10 in Galaxiidae, 2 in Prototroctidae and 5 in Eleotridae; all families present in the freshwater systems of New Zealand today. Correlation with putative related extant taxa reveal that the fishes from the Bannockburn Formation were relatively large, often at the upper margin of the extant sizes of fishes in the respective groups or even larger. This 'Gulliver' fish fauna is consistent with other fossil and extant 'gulliverisms' observed in various Zealandian biota. Environmental and putative evolutionary explanations, aspects of the taphocoenosis and possible stratigraphic implications of the otolith assemblages are discussed.